2008
DOI: 10.1057/rlp.2008.14
|View full text |Cite
|
Sign up to set email alerts
|

Mall development and operations: An Indian perspective

Abstract: a faculty with the Institute of Technology and Management in the area of Retail and Marketing, has been in academics for the past fi ve years after a brief stint in the industry, where she held the position of Product Manager on her last assignment. She is currently pursuing her PhD with Birla Institute of Technology, Pilani, India. Her research interests are in varied fi elds including shopping center patronage, competitive strategies for small retailers and semiotics. J. Ganguliis currently the Chief Executi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(17 citation statements)
references
References 0 publications
0
17
0
Order By: Relevance
“…The understanding of involvement factors could help mall managers in improving the mall attributes that facilitate involvement. Research on Indian malls have discussed location and fi nancial feasibility of malls 17 and store loyalty behavior. 18 -20 This research would add to the existing Indian mall literature with respect to different mall-related factors and consumer involvement with malls.…”
Section: Research Objectivementioning
confidence: 99%
“…The understanding of involvement factors could help mall managers in improving the mall attributes that facilitate involvement. Research on Indian malls have discussed location and fi nancial feasibility of malls 17 and store loyalty behavior. 18 -20 This research would add to the existing Indian mall literature with respect to different mall-related factors and consumer involvement with malls.…”
Section: Research Objectivementioning
confidence: 99%
“…The economic relationship concerns the degree of dependency between the attractiveness of shopping malls and shoppers ' personality traits in reference to the market share, returns on investment and profi tability ( Rajagopal, 2008a ). Two types of shopping centre models are observed in the emerging real estate markets in developing countries, which are characterized by their ultimate relationship with the physical shopping centre on whose web site they reside ( Dixon and Marston, 2005 ;Kuruvilla and Ganguli, 2008 ). It is observed that agglomerations of small stores selling similar ranges of goods around the shopping malls also cause congestion and often divert attraction of price sensitive shoppers towards unfamiliar brands (for example Blois et al , 2001 ).…”
Section: Routes To Market and Shopping Behaviourmentioning
confidence: 99%
“…The economic relationship concerns the degree of dependency between the attractiveness of shopping malls and shoppers ' personality traits in reference to market share, returns on investment and profi tability ( Rajagopal, 2008a ). Two types of shopping centre model are observed in the emerging real estate markets in developing countries, which are characterised by their ultimate relationship with the physical shopping centre on whose web site they reside ( Dixon and Marston, 2005 ;Kuruvilla and Ganguli, 2008 ). The underlying success factors of planned, centrally managed and large shopping malls in the retailing sector rotates around customer satisfaction in reference to selection, atmosphere, convenience, salespeople, refreshments, location, promotional activities and merchandising policy ( Anselmsson, 2006 ).…”
Section: Literature Review and Framework Of Hypotheses Location And Smentioning
confidence: 99%